Multicultural Narrative of History Textbook - Afiyadi, Akhmad Dwi; Sutimin, Leo Agung; Sunardi, Sunardi (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4150, 2018)
Abstract: History textbook is a student’s handbook used in a process of learning history with 2013 Curriculum. That textbook used a popular regressive approach. Through the textbook, students were invited to observe historical events in everyday life and also events occurred. The researchers analyzed the textbook using Discourse-Historical Approach by Ruth Wodak. The approach included three layers of analysis namely; textual analysis, contextual analysis, and prospective criticism analysis. The multicultural narrative contextually can be found throughout the book, especially in the categorization of historical relics in spatial and historical events in the spatial. Textual and contextual meanings can be the basis or paradigm of education policy and praxis as a multicultural competence that is owned by the students themselves, both in solving problems in the classroom as well as in human life. Textbook is important for educational purposes in this area of multicultural competence. Tthe continuation of this book for further analysis in the field of education is quite open, for example in the learning model with other relevant material and so on. The researchers suggest for developing the book, both from the material field and exploring the potential possessed by students to transmit the multicultural values of books to students.